Cardiovascular adverse events in multiple myeloma patients - Heckmann, Markus B.; Doroudgar, Shirin; Katus, Hugo; Lehmann, Lorenz (Journal of thoracic disease, 2018)
Multiple myeloma is a malignant disease, caused by an uncontrolled clonal proliferation of a specific group of white blood cells, the plasma cells. Clinical manifestations include bone pain due to osteolysis, hypercalcemia, anemia, and renal insufficiency. Proteasome inhibitors have substantially improved survival of patients suffering from multiple myeloma, providing an efficient treatment option mainly for relapsed and refractory multiple myeloma. Although constituting one substance class, bortezomib, carfilzomib, and ixazomib differ greatly regarding their non-hematologic side effects. This article reviews the clinical and preclinical data on approved proteasome inhibitors in an attempt to decipher the underlying pathomechanisms related to cardiovascular adverse events seen in clinical trials.
Gesehen am 23.10.2019